Detecção de Campylobacter spp. Em amostras de abatedouros avícolas - Cisco, Isabel Cristina (2015)
Campylobacteriosis is an emerging foodborne zoonotic disease caused by bacteria of the genus Campylobacter spp. where C. jejuni and C. coli are the major species involved in eating disorders and poultry and poultry products reported as primary sources of disease transmission. The difficulties for isolation and quantification of Campylobacter for conventional microbiology encouraged the application of molecular diagnostic techniques, such as the methods of polymerase chain reaction (PCR), which have been used in epidemiological studies with fast and accurate results. The aims of this work were to verify the contamination by Campylobacter spp. in broiler batches, from arrival to slaughterhouses until the final products, by conventional methods of microbiology, multiplex-PCR and realtime PCR for identification of Campylobacter jejuni, Campylobacter coli and C. lari. Three inspected slaughterhouses in northern of Rio Grande do Sul, carrying out two collections in each of them. The samples were collected with three replications, in six points: reception of live birds (cloacal swabs and sponges surface transport cages before and after sanitation); carcass after chilling, refrigerated at 4oC and frozen -12oC, totaling 108 samples. The results demonstrated the presence of Campylobacter spp. in all sampled points, the two detection methods. Thermophilic species contamination (Campylobacter jejuni and C. coli) in products for human consumption, such as cooled and frozen carcasses, is concern for public health, since these products cooked inappropriately or agents of cross-contamination are potentially capable of causing food-borne illness